Analyzing web descriptions of cybersecurity breaches in the healthcare provider sector: A content analytics research method. Issue 129 (June 2023) - Lee, In
Abstract: Though the ever-increasing data breach incidents in healthcare providers are exposing their clients' personal, financial, and medical data to cybercriminals, there is limited empirical research on the dynamics of data breaches. These dynamics include relationships between data breach types and locations, vulnerabilities, and mitigation efforts. To address the research gap, a four-step content analytics-based research method is developed. Firstly, the types of data breaches that take place at various data breach locations are analysed. Secondly, co-occurring keywords are identified from web descriptions of data breach incidents. Thirdly, multi-level themes related to keywords are derived. Lastly, themes and contextual information are translated into vulnerabilities, impacts, and mitigation efforts. The identified vulnerabilities, impacts, and mitigation efforts of the different breach type/location combinations aim to assist practitioners in the prevention and mitigation of cybersecurity breaches.